2018
DOI: 10.2320/matertrans.m2017319
|View full text |Cite
|
Sign up to set email alerts
|

Clinching of Similar and Dissimilar Sheet Materials of Galvanized Steel, Aluminium Alloy and Titanium Alloy

Abstract: Aimed to describe the clinching join-abilities of galvanized steel with aluminium alloy and titanium alloy, extensible die clinched joints were prepared for similar and dissimilar sheet materials combinations. The quality of the clinched joints was analysed from the aspects of material forming, load-bearing capacity and failure modes. The failure mechanism of the clinched joints was researched from macroscopic and microscopic aspects. The results show that the sheet materials which have better strength and har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The results indicated that the preforming of the lower plate can enlarge the mechanical interlock value to some extent, causing the enhancement of the joint strength 15 . In terms of the MCT with an extensible die, Lambiase et al 17 and Chu et al 18 researched the forming mechanism of the MCT with an extensible die for joining various metal materials. Lambiase et al 17 indicated that the flow stress and ductility of connected sheets are the major factors affecting the connectivity of the two materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the preforming of the lower plate can enlarge the mechanical interlock value to some extent, causing the enhancement of the joint strength 15 . In terms of the MCT with an extensible die, Lambiase et al 17 and Chu et al 18 researched the forming mechanism of the MCT with an extensible die for joining various metal materials. Lambiase et al 17 indicated that the flow stress and ductility of connected sheets are the major factors affecting the connectivity of the two materials.…”
Section: Introductionmentioning
confidence: 99%
“…Lambiase et al 17 indicated that the flow stress and ductility of connected sheets are the major factors affecting the connectivity of the two materials. From the study of Chu et al, 18 it is clear that the configuration in which the plates are combined also affects the joint performance. Furthermore, the failure mechanism and failure mode of clinched joints manufactured by MCT with extensible dies were determined according to the investigations of Zhang et al 19 and Lei et al, 20 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Nowadays, the main materials used in the automobile body lightweight structure manufacture field are AA5052, AA5182, AA6061, AA6111, and high-strength steel sheets. 19,20 However, the joining of aluminum alloy materials has always been an obstacle to restrict the application of aluminum alloy. 21 There are several commonly methods, such as selfpierce riveting, spot welding, friction stir welding, [22][23][24] ultrasonic-assisted friction stir welding, 25,26 laser welding, adhesive bonding, and mechanical clinching, which conventionally can be implemented for joining aluminum alloy materials and other lightweight materials.…”
Section: Introductionmentioning
confidence: 99%
“…31 The mechanical clinching process is the most economical and direct method of the aluminum alloy joint forming process. Compared with the conventional joining method, in addition to prominent advantages of economy, energy saving, environmental friendly, 3,19 mechanical clinching also has excellent mechanical properties, particularly the fatigue property. 13 Mechanical clinching is also suitable for joining the heterogeneous and special-shaped covering parts with coating or paint on the surface of the material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation